Ex vivo infection model for Francisella using human lung tissue - Köppen, Kristin; Fatykhova, Diana; Holland, Gudrun; Rauch, Jessica; Tappe, Dennis; Graff, Mareike; Rydzewski, Kerstin; Hocke, Andreas C.; Hippenstiel, Stefan; Heuner, Klaus (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Tularemia is mainly caused by Francisella tularensis (Ft) subsp. tularensis (Ftt) and Ft subsp. holarctica (Ftt) in humans and in more than 200 animal species including rabbits and hares. Human clinical manifestations depend on the route of infection and range from flu-like symptoms to severe pneumonia with a mortality rate up to 60% without treatment. So far, only 2D cell culture and animal models are used to study Francisella virulence, but the gained results are transferable to human infections only to a certain extent. Method In this study, we firstly established an ex vivo human lung tissue infection model using different Francisella strains: Ftt Life Vaccine Strain (LVS), Ftt LVS ΔiglC, Ftt human clinical isolate A-660 and a German environmental Francisella species strain W12-1067 (F-W12). Human lung tissue was used to determine the colony forming units and to detect infected cell types by using spectral immunofluorescence and electron microscopy. Chemokine and cytokine levels were measured in culture supernatants. Results Only LVS and A-660 were able to grow within the human lung explants, whereas LVS ΔiglC and F-W12 did not replicate. Using human lung tissue, we observed a greater increase of bacterial load per explant for patient isolate A-660 compared to LVS, whereas a similar replication of both strains was observed in cell culture models with human macrophages. Alveolar macrophages were mainly infected in human lung tissue, but Ftt was also sporadically detected within white blood cells. Although Ftt replicated within lung tissue, an overall low induction of pro-inflammatory cytokines and chemokines was observed. A-660-infected lung explants secreted slightly less of IL-1β, MCP-1, IP-10 and IL-6 compared to Ftt LVS-infected explants, suggesting a more repressed immune response for patient isolate A-660. When LVS and A-660 were used for simultaneous co-infections, only the ex vivo model reflected the less virulent phenotype of LVS, as it was outcompeted by A-660. Conclusion We successfully implemented an ex vivo infection model using human lung tissue for Francisella. The model delivers considerable advantages and is able to discriminate virulent Francisella from less- or non-virulent strains and can be used to investigate the role of specific virulence factors.